Wiener LMS channel estimation and tracking algorithm for OFDM systems with transmitter diversity - BAI Bin-feng1; CAI Yue-ming1; XU Xin1 (Tongxin xuebao, 2006)
A Wiener LMS channel estimating and tracking algorithm for OFDM systems with transmitter diversity was proposed. The algorithm used Wiener prediction technology to improve the ability of tracking channel. The simulation results show that the algorithm achieve reliable channel estimation. The performance is improved greatly compared with conventional algorithm LMS algorithm and simplified algorithm proposed by LIYe and this improvement is obvious under fast varying channel.